Analisis Nilai Kalor dan Laju Pembakaran Briket Tempurung Kelapa dan Limbah Sampah Plastik - Aisiyah, Muktamar Cholifah (Lembaga Yasin AlSys, 2022)
This research is motivated by making alternative energy from waste. Currently, the waste problem is dominated by plastic waste. The most common use of plastic waste is plastic bags for shopping. This results in accumulation of waste. Briquettes are an alternative energy. The best briquettes are from coconut shells. This study made briquettes from coconut shells with added plastic waste with variations of 0%, 5%, 10%, 15% and 20%. Making briquettes goes through several stages, namely flouring the basic ingredients, making dough, molding and characterization. The characterization results show that the greater the added value of plastic waste, the greater the calorific value produced. This can affect the value of the briquette burning song. Maximum results were obtained from coconut shell briquettes with the addition of 25% plastic waste, namely 8261.2 cal/g.